2011
DOI: 10.4018/jisss.2011070105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adaptivity and Other External Variables on Mobile Service Adoption

Abstract: User Interfaces act as the interaction layer between human and computer and have an important role in system adoption. According to technology acceptance model, acceptance of a system is explained as a function of perceived usefulness and perceived ease of use. Since there are several external variables that have an impact on those variables, the content and interface design of every single application should be addressed specifically to enhance users’ intention to use the system. Adding adaptive features into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Polat et al [44], Phan et al [45] and Kargin et al [46,47] explored the adoption of mobile services using models based on technology acceptance model. Ozen et al [48,49] studies the adoption of online services using similar models.…”
Section: Methodsmentioning
confidence: 99%
“…Polat et al [44], Phan et al [45] and Kargin et al [46,47] explored the adoption of mobile services using models based on technology acceptance model. Ozen et al [48,49] studies the adoption of online services using similar models.…”
Section: Methodsmentioning
confidence: 99%
“…Phan and Daim (2011) and Phan et al (2010) confirmed the framework though additional studies in the US. Polat et al (2011) built upon it and introduced the adaptivity aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lastly, a quantitative study was conducted. During the framework development of this study, a series of empirical studies were performed (Polat, Basoglu, and Daim, , ).…”
Section: Research Frameworkmentioning
confidence: 99%